Back to basics: "hunt for food": wildlife industry to regulate game meat - van der Merwe, M., author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
The 2014-2016 Montreal - Sustainable Wildlife Management Progress Report (Canada, 25-30 April 2016) listed two of the four integral thematic areas as: wildlife and food security and animal and human health. This sentiment echoed from WRSA 15 years ago when vast proportions of financial investment, resources and expertise were applied to finalizing the legal framework for game meat in South Africa. Following the failure of these efforts, further work was initiated to investigate the alternative of an international guideline for the safe production of game meat in SA. Self-regulation was considered the only option left for the game industry in SA with WRSA acknowledging the future small but tangible role of government in the process. The recent "Wildlife Lab" (April - May 2016) initiative, driven by relevant and involved SA Ministers in the wildlife realm, was tasked to bring innovation but practical executable solutions to the challenges in the game industry. The main objective being a totally deracialised game meat industry with safe, legal production of a quality and nutritious protein food which will help address food security in SA and secondly, to empower local communities, BBE's and SMME's through wealth development thereby increasing the industry's contribution to GDP. This R490 million investment proposal provides for inter alia the current game numbers projected growth to 2021 and 2030 with the build-on concurred initiatives. This model will be explained and rolled out based on the 72% financial contribution from the private sector, 22% new entrepreneur funding and 6%institutional support from the SA government. Furthermore, the model highlighted the need for legal guidelines for game meat production and spurred the long overdue publication of the Game Regulations for public comments. In addition, this model and its foreseen successes for game meat production as proposed by the Wildlife Lab could be carbon copied for and maybe the only solution to re-instating the safe and sustainable utilization of bush meat. Correlations between wildlife hunting and bush meat hunting are: both are part of the customary sustainable use of biodiversity to fulfil nutritional protein needs, both are done for economic gain with meat sold in markets, irrespective of being legal or not. However, the difference lies in that: bush meat hunting is the result of an unmanaged common resource being unsustainably harvested due to weak governance, inadequate policy frameworks, and limited data and knowledge. Wildlife hunting on the other hand takes place generally on privately owned land where the land owner also has ownership of the animals, manages these knowledgeably and harvests the resources sustainably resulting in a huge growth in game numbers. In view of its ecological, social and economic value, wildlife is an important renewable natural resource, with significance for areas such as rural development, land-use planning, food supply, tourism, scientific research and cultural heritage. If sustainably managed, wildlife can provide economic- and food security and contribute considerably to the alleviation of poverty as well as to safeguard human and environmental health.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.